2017
DOI: 10.1017/s1355770x17000067
|View full text |Cite
|
Sign up to set email alerts
|

The livelihood impacts of the Equitable Payments for Watershed Services (EPWS) Program in Morogoro, Tanzania

Abstract: ABSTRACT. Research on PES programs in agro-ecosystems is recent and limited in developing countries. The authors use a multi-method, quasi-experimental impact evaluation approach to examine direct and indirect livelihood impacts of the Equitable Payments for Watershed Services (EPWS) program piloted in the Morogoro region in Tanzania. The evaluation is based on a survey of 116 program participants and 117 non-participants, 32 semi-structured interviews and 16 focus group discussions to complement the survey da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 70 publications
2
18
0
2
Order By: Relevance
“…Appropriate Critical Credible n/a n/a Moderate quality Branca (2011) N Y N N n/a n/a n/a n/a n/a n/a Critical quality Kwayu (2017) N Y Y N n/a n/a n/a n/a n/a n/a Critical quality Lopa (2012) N Y Y N n/a n/a n/a n/a n/a n/a Critical quality Bremer (2013 n/a n/a n/a n/a n/a n/a Critical quality Pagiola (2010) n/a n/a n/a n/a n/a n/a Critical quality Chen (…”
Section: Study Typementioning
confidence: 99%
“…Appropriate Critical Credible n/a n/a Moderate quality Branca (2011) N Y N N n/a n/a n/a n/a n/a n/a Critical quality Kwayu (2017) N Y Y N n/a n/a n/a n/a n/a n/a Critical quality Lopa (2012) N Y Y N n/a n/a n/a n/a n/a n/a Critical quality Bremer (2013 n/a n/a n/a n/a n/a n/a Critical quality Pagiola (2010) n/a n/a n/a n/a n/a n/a Critical quality Chen (…”
Section: Study Typementioning
confidence: 99%
“…Defensible Appropriate Critical Credible n/a n/a Moderate quality Bennett (2008) Y Y N N n/a n/a n/a n/a n/a n/a Critical quality Zhang (2008) N Y N N n/a n/a n/a n/a n/a n/a Critical quality Branca (2011) N Y N N n/a n/a n/a n/a n/a n/a Critical quality Kwayu (2017) N Y Y N n/a n/a n/a n/a n/a n/a Critical quality Lopa (2012) N Y Y N n/a n/a n/a n/a n/a n/a Critical quality…”
Section: Plans For Updating the Reviewmentioning
confidence: 99%
“…), and 3) measured the impact on at least one indicator which reflects the overall livelihood status such as total income, total consumption expenditure and/or gross value of household assets. Based on these criteria, studies such as those of Antle (2008), Cole (2010) and their co-authors were not included because their evaluation methods were beyond the scope of this study; studies such as those of Robalino (2014), Sims (2017) and their co-authors were not included because the impact was not measured at the household level; studies such as those of Bravo-Ureta (2011), Kwayu (2017) and their co-authors were not included because their livelihood indicators were unable to reflect the overall livelihood status of ES suppliers. This left us with 27 primary evaluation studies, as shown in Table A1.…”
Section: A2 Inclusion Criteriamentioning
confidence: 99%